Resolva a equação do 1º grau (x-1) (x-3) = 0
Soluções para a tarefa
Respondido por
1
(x-1)(x-3)=0
x²-3x-x+3=0
x²-4x+3=0
x=4 (mais ou menos)![\sqrt{16-12} \sqrt{16-12}](https://tex.z-dn.net/?f=+%5Csqrt%7B16-12%7D+)
2
x= 4 (mais ou menos) 2
2
x' = 3
x'' = 1
x²-3x-x+3=0
x²-4x+3=0
x=4 (mais ou menos)
2
x= 4 (mais ou menos) 2
2
x' = 3
x'' = 1
Perguntas interessantes
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás